THE PROBLEM OF DEVELOPING THE ARTISTIC AND CREATIVE ABILITIES OF FUTURE VISUAL ARTS TEACHERS AND ITS ROLE IN THE HIGHER EDUCATION SYSTEM - Ikromov Muhammad Anaskhan Hakimjon son (American Journals Publishing, 2023)
The article examines the problem of developing artistic and creative abilities of future teachers of fine arts and its place in the higher education system, methods of implementing integrative communication between them based on the use of active teaching methods.
Keywords: pedagogical education, profession, professional competence, professional skill, professional skill.